APLIKASI BERBASIS ANDROID “MENSTRUASI SEHAT” UNTUK MENGATASI DISMENORHOE PADA REMAJA PUTRI - Suptiani, Laila Putri; Kurnia, Herni (Jurnal Medikes (Media Informasi Kesehatan), 2024)
Background: Dysmenorrhea causes 14% of patients to miss school frequently. On March 11, 2020, the World Health Organization (WHO) explained that the disease outbreak caused by the COVID-19 virus was a global pandemic. The Covid-19 pandemic has changed the pattern of life in the community. Including one of the needs for technology. Objective: This study aims to design an android-based application in overcoming Dismenorhoe in Young Women. Method: R&D or Research and Development. Results: The product produced in this study is an android application that contains material about menstruation, dysmenorrhea and dysmenorrhea treatment. Conclusion: Healthy menstrual applications are appropriate to use to treat dysmenorhoe in adolescent girls. Keywords : Application, Dismenorhoe, Healthy Menstruation